Recurrent Streptococcus pneumoniae meningitis and Mondini dysplasia: Association or causation? - Indar K. Sharawat; Ananthanarayanan Kasinathan; Guru P. Peruri; Arushi G. Saini; Naveen Sankhyan; Akshay K. Saxena; Paramjeet Singh (Elsevier, 2019)
Mondini dysplasia is a developmental disorder of the inner ear structures and it is a rare cause of recurrent bacterial meningitis in children. A 10-year-old boy presented with acute febrile encephalopathy and right ear pain. In the past, he had suffered from two distinct episodes of pyogenic meningitis. On examination, he had signs of meningeal irritation and right ear sensorineural deafness. Magnetic resonance imaging of the brain and computerized tomography of the temporal bone was suggestive of Mondini dysplasia in the right ear. Our case highlights the need for (a) screening of hearing loss at the bedside by Rinne and Weber test in case of recurrent bacterial meningitis (b) searching for an underlying inner ear malformation if there is a hearing loss. Keywords: Recurrent meningitis, Mondini dysplasia, Cerebrospinal fluid, Sensorineural hearing loss